2006
DOI: 10.1177/0017896906066067
|View full text |Cite
|
Sign up to set email alerts
|

Motivation for weight-loss diets: A clustering, longitudinal field study using self-esteem and self-determination theory perspectives

Abstract: Background Gradual elevation of body weight leads numerous individuals to dieting and weight loss behaviours. Nevertheless, the prevalence of obesity continues to rise in industrialised countries. The examination of the motivational determinants of dietary modification ('dieting') in order to identify clusters of individuals in the first 6 months of their effort to control body weight was the aim of the current study. The theories of self-determination and self-esteem formation guided our analysis. Methods A l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
9
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 30 publications
5
9
0
Order By: Relevance
“…Questionnaires were sent to all 399 respondents who completed the questionnaire at T1, but only 207 (52%) questionnaires were completed and returned. Similar attrition rates were observed in another longitudinal study by Georgiadis, Biddle, and Stavrou (). Similar to our research, this study applied SDT to determine motivation in a weight management context, and had three time points over a 4‐ to 6‐month period.…”
Section: Methodssupporting
confidence: 86%
See 1 more Smart Citation
“…Questionnaires were sent to all 399 respondents who completed the questionnaire at T1, but only 207 (52%) questionnaires were completed and returned. Similar attrition rates were observed in another longitudinal study by Georgiadis, Biddle, and Stavrou (). Similar to our research, this study applied SDT to determine motivation in a weight management context, and had three time points over a 4‐ to 6‐month period.…”
Section: Methodssupporting
confidence: 86%
“…Again, a similar attrition rate from the second to third time point was found in the study by Georgiadis et al. ().…”
Section: Methodssupporting
confidence: 85%
“…Similar difficulties with a perceived lack of motivation of people with ID in adopting a healthy lifestyle patterns, and especially in engaging in physical activities, have been also reported in other studies (Messent et al 1998). However, motivation to make lifestyle changes can be influenced by different factors (Georgiadis et al 2006) and may be only partially relevant to cognitive impairments. A study has shown that improved self-image is a greater motivator in women than in men and personal health has a bigger influence on the motivation of older people, and men (Satia et al 2001).…”
Section: Barriers and Solutionssupporting
confidence: 73%
“…1998). However, motivation to make lifestyle changes can be influenced by different factors (Georgiadis et al . 2006) and may be only partially relevant to cognitive impairments.…”
Section: Discussionmentioning
confidence: 99%
“…The post-surgical changes in patients’ self-esteem is noteworthy, since poor self-esteem can deteriorate their prognosis and increase the risk of post-op weight regain according to the study by Georgiadis (42). In the current study, there was no significant difference between the pre- and post-operative scores of self-esteem.…”
Section: Discussionmentioning
confidence: 99%